ANALISIS DEBIT SUNGAI SAMBONG KABUPATEN BATANG DENGAN HEC-RAS - ikhwan, Ikhwanudin; Yudaningrum, Farida; Adzkiannisa, Rifka Ahmida (Fakultas Teknik Universitas Tunas Pembangunan Surakarta, 2025)
The Sambong River is located in Batang District, with relatively flat topography and proximity to the sea, making it prone to frequent flooding. As observed in the past three years, the largest flood occurred on January 2, 2023, at 11 points in Batang District, which indirectly caused significant losses to the surrounding community. Therefore, a study is needed to determine the rise in water levels and the flood discharge volume of the Sambong River and to analyze its ability to accommodate such discharge.In this study, the flood discharge analysis for the planned Sambong River was calculated using the Nakayasu HSS method, and the river flow conditions were simulated using the HEC-RAS program with the unsteady flow method. Several data and parameters were based on the existing conditions of the river, resulting in the following discharge values: Q5 319.787 m³/s, Q10 381.146 m³/s, Q25 460.936 m³/s, Q50 521.907 m³/s, and Q100 584.437 m³/s. Based on the HEC-RAS simulation results from 66 STA observation points, it was found that for the Q5 and Q10 return periods, 88% of the STA locations flooded; for the Q25 return period, 91% of STA locations flooded; for the Q50 return period, 92% flooded; and for the Q100 return period, 95% of STA locations flooded, with varying flood heights. Therefore, it can be concluded that the Sambong River is no longer able to accommodate the planned flood discharge